Knowledge and Attitude of Nurses with Computerized Based Nursing Care Documentation - Antonius Janggeng; Sondang Ratnauli Sianturi; Rosa Nora Lina (Media Keperawatan Indonesia, 2022)
The completeness of the implementation of nursing care documentation is part of the quality of services in hospitals that are influenced by the knowledge and attitude of nurses. This study aims to identify the relationship between the knowledge and attitudes of nurses with the completeness of computerized-based nursing care documentation. This research is quantitative research with a descriptive correlation design and cross-sectional approach. The research population were a nurse at the inpatient unit and outpatient unit of Hospital X North Jakarta. The samples used were purposive techniques with 121 respondents. Univariate analysis of nurse knowledge obtained fewer knowledge data with 40 respondents (33.1%) knowledge of 10 respondents (8.3%) and good knowledge of 71 respondents (58.7%) for attitudes, nurses had less attitude with 57 respondents (47.1%) and good attitude of 64 respondents (52.9%). The results of bivariate research show that: there is a meaningful relationship between the knowledge and attitude of nurses with the completeness of documenting computerized-based nursing care at Hospital X North Jakarta, namely knowledge (p value= 0.000) and attitude (p-value = 0.000). The advice in this study is the improvement and development of training for nurses in implementing computerized-based nursing care documentation. So that the development of science from nurses on computerized-based documentation can be carried out properly.